2010
DOI: 10.1016/j.ydbio.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early human neural crest development

Abstract: The outstanding migration and differentiation capacities of neural crest cells (NCCs) have fascinated scientists since Wilhelm His described this cell population in 1868. Today, after intense research using vertebrate model organisms, we have gained considerable knowledge regarding the origin, migration and differentiation of NCCs. However, our understanding of NCC development in human embryos remains largely uncharacterized, despite the role the neural crest plays in several human pathologies. Here, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
143
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 100 publications
(191 reference statements)
14
143
0
Order By: Relevance
“…Therefore, our results demonstrating disruption of the stabilized microtubule network on the basal side of the lung epithelium in Sox9 LOF lungs, and the disorganized microtubule network observed in Sox9 LOF distal epithelial cells in the in vitro migration assay, may be explained by perturbations in the ECM. Although the link between Sox9 and cell migration/microtubule organization may be indirect, in other systems Sox9 is critical for cell migration, including neural crest cells during development (73) and tumor metastasis in breast, colon, prostate, and melanoma cancers (74)(75)(76)(77). In future studies, it will be pertinent to determine how Sox9 is mechanistically regulating acetylated tubulin and epithelial cell movement during lung branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results demonstrating disruption of the stabilized microtubule network on the basal side of the lung epithelium in Sox9 LOF lungs, and the disorganized microtubule network observed in Sox9 LOF distal epithelial cells in the in vitro migration assay, may be explained by perturbations in the ECM. Although the link between Sox9 and cell migration/microtubule organization may be indirect, in other systems Sox9 is critical for cell migration, including neural crest cells during development (73) and tumor metastasis in breast, colon, prostate, and melanoma cancers (74)(75)(76)(77). In future studies, it will be pertinent to determine how Sox9 is mechanistically regulating acetylated tubulin and epithelial cell movement during lung branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In these embryos, Pax3, Sox9 and Sox10 have been detected in premigratory NC, whereas migrating NC cells additionally expressed Ap2a and Pax7. 73 Importantly, a recent study revealed that NC induction in hESCs is preceded by the expression of NPB markers Pax3, Pax7, Msx1 and Ap2a, shortly after also the NC marker snail2 is detected. This study further demonstrated that NC induction in hESCs requires Wnt/b-Catenin, BMP and FGF signaling, which indicates that the basic mechanisms of early NPB and NC induction are also conserved in humans.…”
Section: From Npb To Ncmentioning
confidence: 99%
“…The expression of PAX3, SOX9, and SOX10 in premigratory NC cells and that of PAX7, SOX9, AP2a, and p75 NTR in migratory NC cells has been demonstrated in addition to the expression of SOX10 in human embryos (Betters et al, 2010). Overall, these results indicate that SOX10 and other NC marker genes, in addition to p75 NTR and HNK1, are required for the definitive characterization of NC cells in vivo and in vitro.…”
Section: B C a 26 S Mimura Et Almentioning
confidence: 72%
“…However, a previous study reported that both p75 NTR− and p75 NTR+ cells express other NC markers and are able to differentiate into NC cell derivatives in vitro (Curchoe et al, 2010). A further study of migratory NC cells in early human embryos demonstrated that in vivo p75 NTR+ /HNK1 + cells were localized to a small subset of migratory NC cells and cells of the ventral neural tube in vivo (Betters et al, 2010). It is likely that additional markers are required for definitive characterization of NC cell subsets derived hESC cultures.…”
Section: Characterization Of Cells Induced By Activation Of Bmp4 Signmentioning
confidence: 91%
See 1 more Smart Citation